A hybrid arc spray forming technique for the manufacture of nickel superalloy IN617 - Sato, A; Taneike, M; Okada, I; Grant, P (2014)
Spray forming produces cast microstructures with comparatively low macro- and micro-structural chemical segregation and is thus well-suited for the manufacture of complex chemistry, multi-component alloys that otherwise show strong elemental segregation. Although spray formed Ni superalloys have shown properties equivalent or superior to their conventionally cast/wrought counterparts, they have not been adopted commercially because of the difficulties in ensuring a high process yield and the complexity and associated cost of large-scale Ni superalloy melting. In this paper, we describe a hybrid arc spray forming (HASF) process in which costly, large-scale alloy melting as pre-cursor to spray forming is avoided by the use of a consumable wire feedstock. To achieve thermal conditions of melt spray forming - essential to produce a refined, polygonal grain structure - a customised secondary atomisation system has been developed. Fe-0.8 wt%C and Ni superalloy IN617 microstructures and preliminary mechanical properties suggested that hybrid arc spray forming may offer an attractive combination of convenience, low cost and mechanical performance. © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.